2022
DOI: 10.3390/ani12192517
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Immunity- and Vitamin D3-Activity-Related Gene Expression of Coccidiosis-Challenged Ross 708 Broilers in Response to the In Ovo Injection of 25-Hydroxyvitamin D3 

Abstract: Effects of the in ovo administration of two vitamin D3 sources (vitamin D3 (D3) and 25-hydroxyvitamin D3 (25OHD3)) on the expression of D3 activity- and immunity-related genes in broilers subjected to a coccidiosis infection were investigated. At 18 d of incubation (doi), five in ovo injection treatments were administrated to live embryonated Ross 708 broiler hatching eggs: non-injected (1) and diluent-injected (2) controls, or diluent injection containing 2.4 μg of D3 (3) or 2.4 μg of 25OHD3 (4), or their com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The possible reason for the differential susceptibilities of male and female embryos to pathogenic agents such as FMG or PECV could be linked to differences in their systematic inflammation or humoral immunity responses to different pathogens. Higher nitric oxide levels have been shown to be linked to decreased growth and immune responses [26,[40][41][42][43]. Mousstaaid et al [44] reported that plasma nitric oxide concentrations were higher in male than female broilers at hatch and at 14 days of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible reason for the differential susceptibilities of male and female embryos to pathogenic agents such as FMG or PECV could be linked to differences in their systematic inflammation or humoral immunity responses to different pathogens. Higher nitric oxide levels have been shown to be linked to decreased growth and immune responses [26,[40][41][42][43]. Mousstaaid et al [44] reported that plasma nitric oxide concentrations were higher in male than female broilers at hatch and at 14 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…Primers and probes were designed for differentiation of PECV (Table 3). The forward and reverse primers were designed according to the procedure described by Fatemi [26]. Real Time PCR assays were performed using a QuantStudio TM 6 Flex Fast 96-Well Real Time PCR System (Applied Biosystems, Foster City, CA, USA).…”
Section: Pcr Proceduresmentioning
confidence: 99%
“…The CD4 cells are linked to T-helper and regulatory T cells [ 42 ]. The mechanism of action of these cells is to inhibit T cell proliferation and cytokine production in order to suppress the immune response, thereby maintaining immune homeostasis [ 43 , 44 ]. In addition to immunity, regardless of the level of inclusion, dietary L-AA has also been shown to improve small intestine morphology [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Global effects and least squares means differences were considered significant at P ≤ 0.05. All data were analyzed using the MIXED procedure of SAS software 9.4 ( SAS Institute, 2013 ; Fatemi et al, 2022 ). Treatment means and LS means comparisons for variables that were not significantly affected by treatment are not described or discussed.…”
Section: Methodsmentioning
confidence: 99%